Effect of the submicellar concentration of bile salts on structural alterations of β-casein micelles. Issue 76 (28th July 2016) - Kuchlyan, Jagannath; Roy, Arpita; Dutta, Rupam; Sen, Swagata; Sarkar, Nilmoni
Abstract : The role of bile salts, sodium deoxycholate (NaDC) and sodium cholate (NaCh), on the self-assembly behavior of β-casein micelles (β-CMs) was investigated using various fluorescence techniques. Abstract : The protein self-assembly behavior of β-casein micelles (β-CMs) is investigated in the presence of two bile salts namely sodium deoxycholate (NaDC) and sodium cholate (NaCh) in an aqueous phosphate buffer solution at pH 7.4. The structural behavior and self-assembling properties of β-CMs in the presence of a submicellar concentration of NaDC and NaCh were studied by steady-state and time-resolved fluorescence spectroscopy, fluorescence correlation spectroscopy (FCS) and dynamic light scattering (DLS). The change of critical micellar concentration (CMC) of β-CMs in the presence of NaDC and NaCh is determined taking pyrene as a fluorescence probe. We carried out fluorescence resonance energy transfer (FRET) studies employing coumarin-153 (C-153) as a donor and rhodamine 6G (R6G), as an acceptor in order to probe the structural and dynamic nature of the aggregates. Through Fluorescence Correlation Spectroscopy (FCS) the translational diffusion of R6G in β-CMs and the presence of NaDC and NaCh provide the structural dynamics of these systems. The results are quite comparable to the hypothesis that bile salts affect protein self-assembly through both changes in aqueous structure as well as employing hydrophobic interactions. All the experimental studies support that NaDC forms larger aggregates through complexation with β-CMs than NaCh because of the more hydrophobic character of NaDC compared to NaCh.